THE ROLE OF NATIONAL VALUES AND THE FAMILY IN UPBRINGING OF THE YOUTH - Shokirov Mubin Rustamovich (Journal of Learning on History and Social Sciences, 2024)
In the following article the issues of educating the young generation in the spirit of national values in the process of deep social reforms, which are one of the most important features of our contemporary country are discussed